Host Immune Response to Clinical Hypervirulent Klebsiella pneumoniae Pulmonary Infections via Transcriptome Analysis - Langhuan Lei; Xiaoli Zhang; Rui Yang; Haiming Jing; Yue Yuan; Zhifu Chen; Qiang Gou; Zhuo Zhao; Jinyong Zhang; Xingyong Wang (Journal of Immunology Research)
Klebsiella pneumoniae (K. pneumoniae), especially those with hypervirulence, is becoming a global concern and posing great threat to human health. Studies on individual immune cells or cytokines have partially revealed the function of the host immune defense against K. pneumoniae pulmonary infection. However, systematic immune response against K. pneumoniae has not been fully elucidated. Herein, we report a transcriptome analysis of the lungs from a mouse pneumonia model infected with a newly isolated K. pneumoniae clinical strain YBQ. Total RNA was isolated from the lungs of mice 48 hours post infection to assess transcriptional alteration of genes. Transcriptome data were analyzed with KEGG, GO, and ICEPOP. Results indicated that upregulated transcription level of numerous cytokines and chemokines was coordinated with remarkably activated ribosome and several critical immune signaling pathways, including IL-17 and TNF signaling pathways. Notably, transcription of cysteine cathepsin inhibitor (stfa1, stfa2, and stfa3) and potential cysteine-type endopeptidase inhibitor (cstdc4, cstdc5, and cstdc6) were upregulated. Results of ICEPOP showed neutrophils functions as the most essential cell type against K. pneumoniae infection. Critical gene alterations were further validated by rt-PCR. Our findings provided a global transcriptional perspective on the mechanisms of host defense against K. pneumoniae infection and revealed some unique responding genes.